GEOPROCESSING TECHNIQUES TO MORPHOMETRIC ANALYSIS OF ALTO AGUA FRIA STREAM WATERSHED - BOFETE (SP) - Nardini, R.C.; Campos, S.; Gomes, L.N.; Ribeiro, F.L.; Pissarra, T.C.T.; Campos, M. (Revista Brasileira de Engenharia de Biossistemas, 2016)
A morphometric analysis of Alto Água Fria stream watersheld – Bofete (SP) has been carried using geoprocessing techniques in Geographic Information System, in order to preserve, rationalizing its use and environmental recovery. The watershed has an area of ​​4012,17 ha and is situated between the geographic coordinates: 22o 57' 41" to 23o 02' 42" S and 48o 11' '29" to 48o 20' 09" WGR. The base map used was a Bofete (SP) planialtimetric letter for the extraction of contours and hydrography, to determine the morphometric indices. The results shows that low values ​​of drainage density associated with the presence of permeable rock, facilitate the infiltration of water into the soil, reducing runoff and the risk of erosion and environmental degradation. The low value of shape factor and circularity index indicates that the watershed tends to be more elongated with less susceptibility to more pronounced floods. The environmental parameter, roughness coefficient, allowed to classify the watershed for agriculture vocation.